A MATHEMATICAL MODEL DEVELOPMENT FOR THE QUASI-STATIC LATERAL COLLAPSE OF THE GENERALISED GEOMETRIC HOLLOW SHAPE - Muhamad Ghazali Kamardan (Tesis, 2014)
The purpose of this research is to develo a general predictive mathematical model of the deformation behaviours for various symmetric geometrical tubes under lateral compression between two flat rigid plates. The mathematical model has been proposed based on rigid, perfectly plastic model and the energy balance method.